Kingdom of Lesotho : 2008 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Kingdom of Lesotho. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This 2008 Article IV Consultation discusses that Lesotho has made significant progress in macroeconomic performance, but the pace of implementation of key structural reforms has been slow. After a decade of low growth, economic activity surged above historic trends, averaging 6.6 percent during 2006-07, driven by the mining, textile, and construction sectors. However, poverty has seen only a modest decline. Executive Directors have commended the authorities for their prudent macroeconomic management, which has contributed to the recent strong economic performance and a continued build-up of international reserves.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet